Fostering the effective usage of risk management in construction - Serpell, Alfredo; Ferrada, Ximena; Rubio, Norma Larissa (Journal of Civil Engineering and Management, 2017)
The effective management of risk is critical for construction projects. However, research findings show that risk management is either not used or done ineffectively in domestic construction projects. One of the primary reasons for this appears to be the lack of risk management (RM) capabilities and knowledge. A study aimed at developing a system for supporting the effective use of RM is presented. The system has been designed so as to provide the required functionality to assist owners and contractors to develop their capabilities to manage risk effectively, including: a) to assess the existing RM organizational maturity and to report on the existing gaps, b) to propose recommendations for improving the organizational RM capabilities in the light of the detected gaps, and c) to help companies with the implementation and improvement of RM within the organization. The system prototype has been successfully applied in several companies that served as initial case studies. It is anticipated that the system will assist clients and contractors to advance effective risk management capabilities and to improve their project risk management performance in the medium range. The system can also be applied in other countries that face the same RM difficulties.